PERBANDINGAN ALGORITMA NAÏVE BAYES DAN C4.5 DALAM MENENTUKAN TINGKAT PENJUALAN MOTOR HONDA - Donni Prabowo; Firman Hidayat; Gagah Gumelar; Dewa Qintoro; Aji Setiawan (LPPM STMIK El Rahma Yogyakarta, 2018)
At this time, the mobility of the community activities will be very high. The mobility of the high society will have an impact to the transportation needs are increasing. Coupled with the opportunities of the community towards taxi online, will have an impact on the number of sales of motorcycles in Indonesia. In this research we will classify the sales data of the motor with rapidminer software by applying two algorithm: Algorithm C45, and Naive Bayes. The second algorithm is a method of classification based on statistics and probability. Two of the above algorithms compared the rate of speed in the best-selling motorcycle classification of data, to get the decision tree the best selling motorcycle was purchased by the society, and should be in more production. Research using Algorithm C45 motor with the lowest prices is the best selling, than Algorithm Naïve Bayes where the best selling honda motor is a type of Scooter, medium of CC, and low price.